1946
DOI: 10.1021/i560157a007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oil-Soluble Petroleum Sulfonates. Extraction-Absorption Method

Abstract: The proposed volumetric method for the determination of magnesium in carbonate ores involves removal of most of the calcium as the sulfate, precipitation of magnesium hydroxide with excess standard alkali, and titration of the excess with a standard acid. When methyl red is used as the indicator, 0.50 A7 sodium hydroxide solution that is not carbonate-free can be satisfactorily used. Any indicator having the same pH range as methyl red could be used, but methyl red was selected because it is used in many labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1949
1949
1957
1957

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Carbon has been reported as an adsorbent for alkyl benzenesulfonate (12,28,30), but under conditions giving quantitative desorption, the benzenesulfonate is not separated from all interfering materials. Alkyl benzenesulfonate can be extracted from hydrochloric acid solutions with chloroform (5) or ether (14), and the present authors found that it can be extracted from 3.6 " sulfuric acid with chloroform. In all these cases, however, the protein interference is increased, because reduction of the pH increases the anionic detergent binding power of proteins (4).…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Carbon has been reported as an adsorbent for alkyl benzenesulfonate (12,28,30), but under conditions giving quantitative desorption, the benzenesulfonate is not separated from all interfering materials. Alkyl benzenesulfonate can be extracted from hydrochloric acid solutions with chloroform (5) or ether (14), and the present authors found that it can be extracted from 3.6 " sulfuric acid with chloroform. In all these cases, however, the protein interference is increased, because reduction of the pH increases the anionic detergent binding power of proteins (4).…”
mentioning
confidence: 50%
“…The validity of the double extraction method has been proved in six ways: (1) by the complete recovery of alkyl benzenesulfonate added to various surface water and sewage samples and to a variety of substances known to interfere with the methylene blue determination; (2) by the elimination of the methylene blue interference caused by materials likely to be present in natural samples; (3) by the infrared characterization and measurement of the alkyl benzenesulfonate isolated from surface water and from sewage by the double extraction technique; (4) by the agreement obtained between the double extraction method and independent infrared determinations; (5) by the failure to recover additional quantities of alkyl benzenesulfonate from surface water or sewage samples by extended treatments; and (6) by the study of the precision of the method and the effect of variables upon the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…This method was not satisfactory if appreciable amounts of water and inorganic salts were present and if the elution of the sulfonates with methanol were not complete. Brooks et al (9) tried to overcome some of the difficulties of the A.S.T.M. D 855 method, as first written in 1944, for the analysis of oil-soluble, sodium petroleum sulfonates.…”
Section: General Analysis Of Syndetsmentioning
confidence: 99%
“…The colloidal properties of the mud are not appreciably affected by salt (45) or other electrolytes. Miscellaneous analytical uses have been developed for fuller's earth, such as a chromatographic adsorbent in the determination of vitamins (3), carbohydrates (34), and oil-soap mixtures (6,26). 1 John Harrison Laboratory, University of Pennsylvania, Philadelphia, Pa. 2 Present address, Houdry Process Corporation, Marcus Hook, Pa.…”
Section: Fuller'smentioning
confidence: 99%